Magnetic properties and concentration of heavy metals in soils and street dust - Yazikov Egor; Osipova Nina; Talovskaya Anna; Osipov Konstantin; Novikov Sergey (EPJ Web of Conferences)
Magnetic susceptibility values of different dust fractions were determined by the kappametry method for the Mezhdurechensk city territory (Kemerovo oblast) exposed to coal mining enterprises. The mineral composition of the dust was studied. The magnetic susceptibilities of soil samples were determined as reference values. The analysis of iron group elements in road dust (size fraction < 1 mm) showed the positive noticeable correlation between the dust magnetic susceptibility and amount of Fe, Co, Cr contained in it. The measurement of the road dust magnetic susceptibility by the kappametry method allows quick assessment of pollution with the heavy metals of the iron group and can be recommended for monitoring.